High-thermal-conductivity liquid silica gel composite material and preparation method thereof

By using physical-chemically modified extra-large scale graphite as thermal filler in liquid silica gel materials, the problem of insufficient thermal conductivity of traditional liquid silica gel materials is solved, and the flexibility and thermal conductivity of the material are improved through chemical modification, achieving a combination of efficient heat dissipation and excellent mechanical properties.

CN119570261APending Publication Date: 2025-03-07DONGGUAN SHIDAI SILICON IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411811607.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional liquid silicone materials have low thermal conductivity, which is difficult to meet the needs of efficient heat dissipation in modern electronic devices and other fields. At the same time, the addition of large-sized scale graphite will lead to material hardening and mechanical properties degradation.

Method used

By introducing extra-large scale graphite treated with oxygen-rich microwave plasma as a thermal filler, and chemically modified under the action of an amino-containing silane coupling agent, silicone oil containing flexible chains is grafted to improve thermal conductivity and flexibility.

Benefits of technology

A high thermal conductivity liquid silicone composite material with a thermal conductivity exceeding 28W/(m·K) was achieved, while avoiding the problem of poor mechanical properties after the introduction of large-size scale graphite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570261A_ABST
    Figure CN119570261A_ABST
Patent Text Reader

Abstract

The invention relates to a high-thermal-conductivity liquid silica gel composite material and a preparation method thereof, and relates to the technical field of liquid silica gel materials, the high-thermal-conductivity liquid silica gel composite material comprises a component A and a component B, the component A is prepared from the following raw materials in parts by weight: 40 to 60 parts of polysiloxane compound, 20 to 35 parts of heat-conducting filler, 20 to 30 parts of vinyl MQ silicon resin and 0.5 to 1.5 parts of catalyst; the component B is prepared from the following raw materials in parts by weight: 40 to 60 parts of polysiloxane compound, 15 to 20 parts of heat-conducting filler, 15 to 25 parts of vinyl MQ silicon resin and the like. On the basis of an existing liquid silica gel base material system, extra-large crystalline flake graphite subjected to physical-chemical combined modification is introduced to serve as a heat conduction filler, the heat conductivity of an existing liquid silica gel material is remarkably improved, and meanwhile the problems that after large-size crystalline flake graphite is introduced, the mechanical property is poor and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of liquid silicone materials, and in particular to a high thermal conductivity liquid silicone composite material and a preparation method thereof. Background Art

[0002] Liquid Silicone Rubber (LSR) is a non-toxic, heat-resistant, highly resilient, flexible, thermosetting, transparent organic silicone material. Its sulfur-transforming behavior is mainly characterized by low viscosity, rapid curing, shear thinning, and a high thermal expansion coefficient. It is widely used in fields such as electronic packaging and sealing. However, the thermal conductivity of traditional liquid silicone materials is low (usually between 0.125-0.25W / (m·k)), which makes it difficult to meet the needs of efficient heat dissipation in fields such as modern electronic devices. Therefore, how to improve the thermal conductivity of liquid silicone materials has become the focus and hotspot of current research.

[0003] In order to improve the thermal conductivity of silica gel, researchers have tried to add high thermal conductivity fillers to silica gel, such as metal oxides (such as Al2O3, MgO, BeO, etc.), metal nitrides (such as SiN, AlN, BN, etc.), graphene and other ceramic powders. The thermal conductivity of these fillers is not only related to the material itself, but also closely related to the particle size distribution, morphology, interface contact, and degree of bonding within the molecule. By optimizing the type, content and dispersion state of the filler, the thermal conductivity of silica gel can be significantly improved. Among them, flake graphite has a large size, high thermal conductivity, low price, and no agglomeration when dispersed in the matrix. The filling amount can be greatly increased, which has obvious advantages in improving thermal conductivity. However, the addition of large-sized flake graphite makes the liquid silicone composite material hard and brittle, and the mechanical properties are reduced, which also limits the further application of flake graphite as a thermally conductive filler. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a high thermal conductivity liquid silicone composite material and a preparation method thereof.

[0005] In a first aspect, the present invention provides a high thermal conductivity liquid silicone composite material, wherein the high thermal conductivity liquid silicone composite material comprises a component A and a component B;

[0006] In parts by weight, the A component includes the following raw materials:

[0007] 40-60 parts of polysiloxane compound, 20-35 parts of thermal conductive filler, 20-30 parts of vinyl MQ silicone resin and 0.5-1.5 parts of catalyst;

[0008] In parts by weight, the B component includes the following raw materials:

[0009] 40-60 parts of polysiloxane compound, 15-20 parts of thermal conductive filler, 15-25 parts of vinyl MQ silicone resin and 0.5-1.5 parts of inhibitor;

[0010] The thermal conductive filler is obtained by subjecting super large flake graphite with a flake diameter of 300 to 500 microns to oxygen-rich microwave plasma treatment and then grafting silicone oil containing flexible chains.

[0011] Furthermore, the component A comprises the following raw materials in parts by weight:

[0012] 55 parts of polysiloxane compounds, 30 parts of thermal conductive fillers, 25 parts of vinyl MQ silicone resins and 1 part of catalyst.

[0013] Furthermore, the B component includes the following raw materials in parts by weight:

[0014] 30 parts of polysiloxane compounds, 17 parts of thermal conductive fillers, 20 parts of vinyl MQ silicone resins and 1 part of inhibitors.

[0015] Furthermore, the weight ratio of the component A to the component B is (1-2):(1-2).

[0016] Furthermore, the polysiloxane compound includes at least one of terminal vinyl polysiloxane and terminal hydrogen-containing polysiloxane.

[0017] Furthermore, the catalyst includes a platinum catalyst.

[0018] Further, the inhibitor includes at least one of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 1-ethynyl-1-cyclohexanol.

[0019] Furthermore, the preparation method of the thermally conductive filler comprises the following process:

[0020] The extra-large flake graphite is placed in a microwave plasma treatment device, oxygen and argon with a volume ratio of 6:1 are introduced as working media, and oxygen-enriched microwave plasma treatment is performed for 5 to 10 minutes under the conditions of a microwave power of 50 to 100 W and a glow discharge mode, and then oxygen is continuously introduced for 5 to 10 minutes to obtain extra-large flake graphite treated with oxygen-enriched microwave plasma;

[0021] The extra-large flake graphite treated with oxygen-enriched microwave plasma, amino-terminated silicone oil, amino-containing silane coupling agent and toluene solvent are stirred and mixed in a weight ratio of (1-2):(0.2-0.5):(0.1-0.3):(15-25), and then refluxed at a temperature of 120-135° C. for 12 hours, cooled, centrifuged and dried to obtain the thermal conductive filler.

[0022] Furthermore, the product model of the amino-containing silane coupling agent includes at least one of KH530, KH550 and KH602; the number average molecular weight of the amino-terminated silicone oil is 1000-2000.

[0023] In a second aspect, the present invention provides a method for preparing the high thermal conductivity liquid silicone composite material according to any one of the first aspects, the preparation method comprising the following steps:

[0024] Stirring and mixing the raw materials in the A component to obtain the A component;

[0025] The raw materials in the B component are stirred and mixed to obtain the B component.

[0026] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:

[0027] The embodiment of the present invention provides a high thermal conductivity liquid silicone composite material. On the basis of the existing liquid silicone base material system, the present invention introduces extra-large flake graphite that has been modified by physical-chemical combination as a thermal conductive filler. On the one hand, after the extra-large flake graphite is physically modified by oxygen-rich microwave plasma, active sites such as hydroxyl and carboxyl groups are directly generated on the surface of graphene. On the other hand, under the action of an amino-containing silane coupling agent, active sites such as hydroxyl and carboxyl groups on the surface of graphene are chemically modified with terminal amino silicone oil, and silicone oil containing flexible chains is grafted thereon in a covalently bonded manner, thereby improving the flexibility, compatibility and thermal conductivity of the extra-large flake graphite. In this way, not only the thermal conductivity of the existing liquid silicone material is improved, and a high thermal conductivity liquid silicone composite material with a thermal conductivity coefficient of >28W / (m·K) is obtained, but also the problem that the introduction of large-size flake graphite will lead to poor mechanical properties is overcome. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0030] Figure 1 A schematic flow chart of a method for preparing a high thermal conductivity liquid silicone composite material provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0033] In a first aspect, the present invention provides a high thermal conductivity liquid silicone composite material, wherein the high thermal conductivity liquid silicone composite material comprises a component A and a component B;

[0034] In parts by weight, the A component includes the following raw materials:

[0035] 40-60 parts of polysiloxane compound, 20-35 parts of thermal conductive filler, 20-30 parts of vinyl MQ silicone resin and 0.5-1.5 parts of catalyst;

[0036] In parts by weight, the B component includes the following raw materials:

[0037] 40-60 parts of polysiloxane compound, 15-20 parts of thermal conductive filler, 15-25 parts of vinyl MQ silicone resin and 0.5-1.5 parts of inhibitor;

[0038] The thermal conductive filler is obtained by subjecting super large flake graphite with a flake diameter of 300 to 500 microns to oxygen-rich microwave plasma treatment and then grafting silicone oil containing flexible chains.

[0039] The embodiment of the present invention provides a high thermal conductivity liquid silicone composite material. On the basis of the existing liquid silicone base material system, the present invention introduces extra-large flake graphite that has been modified by physical-chemical combination as a thermal conductive filler. On the one hand, after the extra-large flake graphite is physically modified by oxygen-rich microwave plasma, active sites such as hydroxyl and carboxyl groups are directly generated on the surface of graphene. On the other hand, under the action of an amino-containing silane coupling agent, active sites such as hydroxyl and carboxyl groups on the surface of graphene are chemically modified with terminal amino silicone oil, and silicone oil containing flexible chains is grafted thereon in a covalently bonded manner, thereby improving the flexibility, compatibility and thermal conductivity of the extra-large flake graphite. In this way, not only the thermal conductivity of the existing liquid silicone material is improved, and a high thermal conductivity liquid silicone composite material with a thermal conductivity coefficient of >28W / (m·K) is obtained, but also the problem that the introduction of large-size flake graphite will lead to poor mechanical properties is overcome.

[0040] In some specific embodiments, the A component includes the following raw materials in parts by weight:

[0041] 55 parts of polysiloxane compounds, 30 parts of thermal conductive fillers, 25 parts of vinyl MQ silicone resins and 1 part of catalyst.

[0042] Furthermore, the B component includes the following raw materials in parts by weight:

[0043] 30 parts of polysiloxane compounds, 17 parts of thermal conductive fillers, 20 parts of vinyl MQ silicone resins and 1 part of inhibitors.

[0044] In some specific embodiments, the weight ratio of the component A to the component B is (1-2):(1-2).

[0045] In some specific embodiments, the polysiloxane compound includes at least one of a terminal vinyl polysiloxane and a terminal hydrogen-containing polysiloxane.

[0046] In some specific embodiments, the catalyst includes a platinum catalyst, such as platinum black, platinum chloride, chloroplatinic acid, etc.

[0047] In some specific embodiments, the inhibitor includes at least one of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 1-ethynyl-1-cyclohexanol.

[0048] In some specific embodiments, the method for preparing the thermally conductive filler includes the following process:

[0049] The extra-large flake graphite is placed in a microwave plasma treatment device, oxygen and argon with a volume ratio of 6:1 are introduced as working media, and oxygen-enriched microwave plasma treatment is performed for 5 to 10 minutes under the conditions of a microwave power of 50 to 100 W and a glow discharge mode, and then oxygen is continuously introduced for 5 to 10 minutes to obtain extra-large flake graphite treated with oxygen-enriched microwave plasma;

[0050] The extra-large flake graphite treated with oxygen-enriched microwave plasma, amino-terminated silicone oil, amino-containing silane coupling agent and toluene solvent are stirred and mixed in a weight ratio of (1-2):(0.2-0.5):(0.1-0.3):(15-25), and then refluxed at a temperature of 120-135° C. for 12 hours, cooled, centrifuged and dried to obtain the thermal conductive filler.

[0051] In some specific embodiments, the product model of the amino-containing silane coupling agent includes at least one of KH530, KH550 and KH602; and the number average molecular weight of the amino-terminated silicone oil is 1000-2000.

[0052] In a second aspect, the present invention provides a method for preparing the high thermal conductivity liquid silicone composite material according to any one of the first aspects, such as Figure 1 As shown, the preparation method comprises the following steps:

[0053] Stirring and mixing the raw materials in the A component to obtain the A component;

[0054] The raw materials in the B component are stirred and mixed to obtain the B component.

[0055] The preparation method of the high thermal conductivity liquid silicone composite material provided by the present invention is simple to operate, does not require additional specific equipment, and is suitable for industrial mass production. When used, component A and component B are mixed in the high thermal conductivity liquid silicone composite material and cured at 160° C. for 5 to 10 minutes.

[0056] It should be noted that the raw material components involved in the high thermal conductivity liquid silicone composite material and its application provided by the embodiments of the present invention, unless otherwise specified or described, can be directly purchased from the market or made in-house according to existing preparation methods; at the same time, the operating steps involved in the preparation method, unless otherwise specified or described, can be carried out according to the existing preparation method of high thermal conductivity liquid silicone composite materials.

[0057] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0058] Example 1

[0059] This example provides a high thermal conductivity liquid silicone composite material, wherein the high thermal conductivity liquid silicone composite material comprises component A and component B in a weight ratio of 1:1;

[0060] In parts by weight, the A component includes the following raw materials:

[0061] 55 parts of terminal vinyl polysiloxane, 30 parts of thermal conductive filler, 25 parts of vinyl MQ silicone resin and 1 part of platinum catalyst;

[0062] In parts by weight, the B component includes the following raw materials:

[0063] 20 parts of terminal vinyl polysiloxane, 10 parts of terminal hydrogen-containing polysiloxane, 17 parts of thermally conductive filler, 20 parts of vinyl MQ silicone resin and 1 part of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane;

[0064] The preparation method of the thermally conductive filler comprises the following steps:

[0065] The super-large flake graphite with a flake size of 500 microns is placed in a microwave plasma treatment device, oxygen and argon with a volume ratio of 6:1 are introduced as working media, and oxygen-enriched microwave plasma treatment is performed for 7 minutes under the conditions of microwave power of 80W and glow discharge mode, and then oxygen is continuously introduced for 8 minutes to obtain super-large flake graphite after oxygen-enriched microwave plasma treatment;

[0066] The extra-large flake graphite treated with oxygen-enriched microwave plasma, the amino-terminated silicone oil with a number average molecular weight of 1000 to 2000, the amino-containing silane coupling agent KH530 and the toluene solvent are stirred and mixed in a weight ratio of 1.5:0.4:0.2:20, and then refluxed at 130° C. for 12 hours, cooled, centrifuged and dried to obtain the thermal conductive filler.

[0067] The preparation method of the above-mentioned high thermal conductivity liquid silicone composite material comprises the following steps:

[0068] Stirring and mixing the raw materials in the A component to obtain the A component;

[0069] Stirring and mixing the raw materials in the B component to obtain the B component;

[0070] The component A and the component B are mixed and then cured at 160° C. for 8 minutes.

[0071] Example 2

[0072] This example provides a high thermal conductivity liquid silicone composite material, wherein the high thermal conductivity liquid silicone composite material comprises component A and component B in a weight ratio of 1:1;

[0073] In parts by weight, the A component includes the following raw materials:

[0074] 40 parts of terminal vinyl polysiloxane, 20 parts of thermal conductive filler, 20 parts of vinyl MQ silicone resin and 0.5 parts of platinum catalyst;

[0075] In parts by weight, the B component includes the following raw materials:

[0076] 20 parts of terminal vinyl polysiloxane, 20 parts of terminal hydrogen-containing polysiloxane, 15 parts of thermally conductive filler, 15 parts of vinyl MQ silicone resin and 0.5 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane;

[0077] The preparation method of the thermally conductive filler comprises the following steps:

[0078] The super-large flake graphite with a flake size of 300 microns is placed in a microwave plasma treatment device, oxygen and argon with a volume ratio of 6:1 are introduced as working media, and oxygen-enriched microwave plasma treatment is performed for 10 minutes under the conditions of microwave power of 50W and glow discharge mode, and then oxygen is continuously introduced for 10 minutes to obtain super-large flake graphite after oxygen-enriched microwave plasma treatment;

[0079] The extra-large flake graphite treated with oxygen-enriched microwave plasma, amino-terminated silicone oil with a number average molecular weight of 1000 to 2000, amino-containing silane coupling agent KH530 and toluene solvent are stirred and mixed in a weight ratio of 1:0.2:0.1:15, and then refluxed at 130° C. for 12 hours, cooled, centrifuged and dried to obtain the thermal conductive filler.

[0080] The preparation method of the above-mentioned high thermal conductivity liquid silicone composite material comprises the following steps:

[0081] Stirring and mixing the raw materials in the A component to obtain the A component;

[0082] Stirring and mixing the raw materials in the B component to obtain the B component;

[0083] The component A and the component B are mixed and then cured at 160° C. for 8 minutes.

[0084] Example 3

[0085] This example provides a high thermal conductivity liquid silicone composite material, wherein the high thermal conductivity liquid silicone composite material comprises component A and component B in a weight ratio of 1:1;

[0086] In parts by weight, the A component includes the following raw materials:

[0087] 60 parts of terminal vinyl polysiloxane, 35 parts of thermal conductive filler, 30 parts of vinyl MQ silicone resin and 1.5 parts of platinum catalyst;

[0088] In parts by weight, the B component includes the following raw materials:

[0089] 40 parts of terminal vinyl polysiloxane, 20 parts of terminal hydrogen-containing polysiloxane, 20 parts of thermal conductive filler, 25 parts of vinyl MQ silicone resin and 1.5 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane;

[0090] The preparation method of the thermally conductive filler comprises the following steps:

[0091] The super-large flake graphite with a flake size of 400 microns is placed in a microwave plasma treatment device, oxygen and argon with a volume ratio of 6:1 are introduced as working media, and oxygen-enriched microwave plasma treatment is performed for 5 minutes under the conditions of microwave power of 100 W and glow discharge mode, and then oxygen is continuously introduced for 5 minutes to obtain super-large flake graphite after oxygen-enriched microwave plasma treatment;

[0092] The extra-large flake graphite treated with oxygen-enriched microwave plasma, the amino-terminated silicone oil with a number average molecular weight of 1000 to 2000, the amino-containing silane coupling agent KH530 and the toluene solvent are stirred and mixed in a weight ratio of 2:0.5:0.3:25, and then refluxed at 130° C. for 12 hours, cooled, centrifuged and dried to obtain the thermal conductive filler.

[0093] The preparation method of the above-mentioned high thermal conductivity liquid silicone composite material comprises the following steps:

[0094] Stirring and mixing the raw materials in the A component to obtain the A component;

[0095] Stirring and mixing the raw materials in the B component to obtain the B component;

[0096] The component A and the component B are mixed and then cured at 160° C. for 8 minutes.

[0097] Comparative Example 1

[0098] This example provides a liquid silicone composite material and a preparation method thereof, which differs from Example 1 only in that the thermal conductive filler is extra-large flake graphite with a sheet diameter of 500 microns (without modification treatment); the remaining steps and parameters are the same.

[0099] Comparative Example 2

[0100] This example provides a liquid silicone composite material and a preparation method thereof. The only difference from Example 1 is that the thermally conductive filler is obtained by treating extra-large flake graphite with a sheet size of 500 microns with oxygen-rich microwave plasma. The specific process is: placing the extra-large flake graphite with a sheet size of 500 microns in a microwave plasma treatment device, introducing oxygen and argon with a volume ratio of 6:1 as the working medium, and conducting oxygen-rich microwave plasma treatment for 7 minutes under a microwave power of 80 W and a glow discharge mode, and then continuing to introduce oxygen for 8 minutes to obtain the thermally conductive filler; the remaining steps and parameters are the same.

[0101] Comparative Example 3

[0102] This example provides a liquid silicone composite material and a preparation method thereof, which differs from Example 1 only in that: the thermally conductive filler is obtained by treating extra-large flake graphite with a flake size of 500 microns with terminal amino silicone oil and an amino-containing silane coupling agent. The specific process is: the extra-large flake graphite with a flake size of 500 microns, terminal amino silicone oil with a number average molecular weight of 1000 to 2000, amino-containing silane coupling agent KH530 and toluene solvent are stirred and mixed in a weight ratio of 1.5:0.4:0.2:20, and then refluxed at 130°C for 12 hours, cooled, centrifuged and dried to obtain the thermally conductive filler; the remaining steps and parameters are the same.

[0103] Test Case

[0104] In this example, the thermal conductivity and mechanical properties of the liquid silicone composite materials provided by Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the liquid silicone composite material obtained in Comparative Example 1 was used as a benchmark to calculate the improvement rates of the thermal conductivity and mechanical properties of the liquid silicone composite materials provided by Examples 1 to 3 and Comparative Examples 2 to 3, respectively. The test results are shown in Table 1 below.

[0105] Table 1

[0106] Test samples Thermal conductivity improvement rate (%) Tensile strength improvement rate (%) Example 1 35% 68% Example 2 20% 41% Example 3 24% 53% Comparative Example 2 8% 12% Comparative Example 3 5% 19%

[0107] In summary, the embodiments of the present invention provide a high thermal conductivity liquid silicone composite material and a preparation method thereof. On the basis of the existing liquid silicone base material system, the present invention introduces extra-large flake graphite that has been physically and chemically modified as a thermally conductive filler. On the one hand, after the extra-large flake graphite is physically modified by oxygen-rich microwave plasma, active sites such as hydroxyl and carboxyl groups are directly generated on the surface of graphene. On the other hand, under the action of an amino-containing silane coupling agent, active sites such as hydroxyl and carboxyl groups on the surface of graphene are chemically modified with terminal amino silicone oil, and silicone oil containing flexible chains is grafted thereon in a covalently bonded manner, thereby improving the flexibility, compatibility and thermal conductivity of the extra-large flake graphite. In this way, not only the thermal conductivity of the existing liquid silicone material is improved, and a high thermal conductivity liquid silicone composite material with a thermal conductivity coefficient of >28W / (m·K) is obtained, but also the problem of poor mechanical properties caused by the introduction of large-size flake graphite is overcome.

[0108] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0109] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A high thermal conductivity liquid silicone composite material, characterized in that: The high thermal conductivity liquid silicone composite material comprises component A and component B; In parts by weight, the A component includes the following raw materials: 40-60 parts of polysiloxane compound, 20-35 parts of thermal conductive filler, 20-30 parts of vinyl MQ silicone resin and 0.5-1.5 parts of catalyst; In parts by weight, the B component includes the following raw materials: 40-60 parts of polysiloxane compound, 15-20 parts of thermal conductive filler, 15-25 parts of vinyl MQ silicone resin and 0.5-1.5 parts of inhibitor; The thermal conductive filler is obtained by subjecting super large flake graphite with a flake diameter of 300 to 500 microns to oxygen-rich microwave plasma treatment and then grafting silicone oil containing flexible chains.

2. The high thermal conductivity liquid silicone composite material according to claim 1, characterized in that: In parts by weight, the A component includes the following raw materials: 55 parts of polysiloxane compounds, 30 parts of thermal conductive fillers, 25 parts of vinyl MQ silicone resins and 1 part of catalyst.

3. The high thermal conductivity liquid silicone composite material according to claim 1, characterized in that: In parts by weight, the B component includes the following raw materials: 30 parts of polysiloxane compounds, 17 parts of thermal conductive fillers, 20 parts of vinyl MQ silicone resins and 1 part of inhibitors.

4. The high thermal conductivity liquid silicone composite material according to claim 1, characterized in that: The weight ratio of the A component to the B component is (1-2):(1-2).

5. The high thermal conductivity liquid silicone composite material according to claim 1, characterized in that: The polysiloxane compound includes at least one of terminal vinyl polysiloxane and terminal hydrogen-containing polysiloxane.

6. The high thermal conductivity liquid silicone composite material according to claim 1, characterized in that: The catalyst includes a platinum catalyst.

7. The high thermal conductivity liquid silicone composite material according to claim 1, characterized in that: The inhibitor includes at least one of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 1-ethynyl-1-cyclohexanol.

8. The high thermal conductivity liquid silicone composite material according to claim 1, characterized in that: The preparation method of the thermal conductive filler comprises the following steps: The extra-large flake graphite is placed in a microwave plasma treatment device, oxygen and argon with a volume ratio of 6:1 are introduced as working media, and oxygen-enriched microwave plasma treatment is performed for 5 to 10 minutes under the conditions of a microwave power of 50 to 100 W and a glow discharge mode, and then oxygen is continuously introduced for 5 to 10 minutes to obtain extra-large flake graphite treated with oxygen-enriched microwave plasma; The extra-large flake graphite treated with oxygen-enriched microwave plasma, amino-terminated silicone oil, amino-containing silane coupling agent and toluene solvent are stirred and mixed in a weight ratio of (1-2):(0.2-0.5):(0.1-0.3):(15-25), and then refluxed at a temperature of 120-135° C. for 12 hours, cooled, centrifuged and dried to obtain the thermal conductive filler.

9. The high thermal conductivity liquid silicone composite material according to claim 8, characterized in that: The product model of the amino-containing silane coupling agent includes at least one of KH530, KH550 and KH602; the number average molecular weight of the amino-terminated silicone oil is 1000-2000.

10. A method for preparing the high thermal conductivity liquid silicone composite material according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: Stirring and mixing the raw materials in the A component to obtain the A component; The raw materials in the B component are stirred and mixed to obtain the B component.